The Effect of Green Accounting, Intellectual Capital, Sales Growth on Financial Performance with GCG Moderation - Ulandari, Monica Novi; Indiraswari, Susmita Dian; Yogivaria, Doni Wirshandono (Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The purpose of the study was to examine the effect of green accounting, intellectual capital, and sales growth on financial performance with GCG as a moderating variable. The study used a quantitative approach, with data obtained from annual reports and sustainability reports available on the official website of the Indonesia Stock Exchange (IDX) and related company websites. The study population included 873 non-financial sector companies in the period 2021–2023. A total of 25 companies met the sample criteria after being selected using the purposive sampling method. The data analysis used the SEM PLS method. The results showed that there was no effect of green accounting on financial performance, but there was a positive effect of intellectual capital and sales growth on financial performance. In addition, GCG was unable to strengthen the relationship between green accounting and sales growth on financial performance, but was able to strengthen intellectual capital on financial performance.